The Mythic Hero and the Wheel: The Narrative Pattern of the Quest Motif in Sam Mendes's "Road to Perdition" - Cristina Flores Moreno (Amaltea: Revista de Mitocrítica, 2011)
It is the main purpose of this paper to explore the narrative pattern of the quest motif in Sam Mendes's Road to Perdition (2002). The study of the narrative structure in Sam Mendes's movie will illustrate that the quest constituent in the road movie genre sometimes acquires the form of a contemporary ‘mechanized’ version of the archetypal hero-adventure as it was described by Campbell in A Hero with a Thousand Faces (1949). The movie is based on a graphic novel by Max Allan Collins and Richard Piers Rayner, though Mendes significantly departs from it to provide the story with a mythic weight that was not present in Collins’s work.